2018
DOI: 10.1093/hmg/ddy292
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X mental retardation protein modulates the stability of its m6A-marked messenger RNA targets

Abstract: N6-methyladenosine (m6A) is the most prevalent internal modification of mammalian messenger RNAs (mRNAs) and long non-coding RNAs. The biological functions of this reversible RNA modification can be interpreted by cytoplasmic and nuclear 'm6A reader' proteins to fine-tune gene expression, such as mRNA degradation and translation initiation. Here we profiled transcriptome-wide m6A sites in adult mouse cerebral cortex, underscoring that m6A is a widespread epitranscriptomic modification in brain. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 74 publications
2
144
0
1
Order By: Relevance
“…More importantly, focusing on FMRP's translational function in dendritic synapses overlooks the fact that the great majority of this protein is located in the cell soma 9 . Indeed, a wide range of research has associated FMRP to multiple steps of the mRNA life cycle, including pre-mRNA splicing 10 , mRNA editing 11,12 , miRNA activity 13,14 , and mRNA stability 15,16 . Additionally, FMRP may function outside the RNA-binding scope, by chromatin binding and regulating genome stability 17,18 , as well as directly binding to and regulating ion channels 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, focusing on FMRP's translational function in dendritic synapses overlooks the fact that the great majority of this protein is located in the cell soma 9 . Indeed, a wide range of research has associated FMRP to multiple steps of the mRNA life cycle, including pre-mRNA splicing 10 , mRNA editing 11,12 , miRNA activity 13,14 , and mRNA stability 15,16 . Additionally, FMRP may function outside the RNA-binding scope, by chromatin binding and regulating genome stability 17,18 , as well as directly binding to and regulating ion channels 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…It would be of critical importance to test whether a similar mechanism also applies to mammals. The FMR1-mediated nuclear export and stability of methylated RNA as recently uncovered may contribute as well to the disease Hsu et al, 2019;Zhang et al, 2018). It is worth mentioning that while our study mainly focuses on two key Fmr1 targets involved in the gross morphology of the nervous system, it is likey that m 6 A and Fmr1 regulate additionnal targets involved in more subtle processes such as synapse functionality and complex trait behaviors.…”
Section: Relevance Of This Interplay In Fxsmentioning
confidence: 80%
“…As a chemical marker, m 6 A has been identified in many animal and plant genes, and exerts effects in important biological pathways [49,50]. Zhou et al showed that HSP70 mRNA containing m 6 A modification sites in the 5 UTR underwent independent translation without depending on the N 7methylguanosine cap, while methylation was increased in the 5 UTR after HSP70 heat shock [20].…”
Section: Discussionmentioning
confidence: 99%